5x² + 5x + 2x + 2
5x(x + 1) + 2(x + 1)
(5x + 2)(x + 1)
Step-by-step explanation:
3x + (2x + 4) is equivalent to (3x + 2x) + 4
because there is no change of signs taking place as there is no (-) sign in front of the brackets
3x + (2x + 4) | (3x + 2x) + 4
3x + 2x + 4 | 3x + 2x +4
5x + 4 | 5x + 4
Answer:
x = 8
Step-by-step explanation:
Step 1 : Simplify the equation
3(x-5) + 7x = 65
3x - 15 + 7x = 65
Step 2 : Make x the subject
3x + 7x = 65 + 15
10x = 80
x = 80/10
x = 8
!!
Answer:
Yes
Step-by-step explanation:
10x5=50
50/60